2022
DOI: 10.1186/s13071-022-05494-2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Folmer primers for the cytochrome c oxidase gene facilitates identification of mosquitoes

Abstract: Background Accurate identification of mosquito species is essential for the development and optimization of strategies to control mosquitoes and mosquito-borne diseases. Problems with the morphological identification of mosquito species have led to the use of molecular identification techniques, in particular the Folmer cytochrome c oxidase subunit I (COI) PCR system (FCOS), originally designed to identify a range of other invertebrates. Methods As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Mounting evidence show that ISVs interact with other components of the mosquito microbiota and influence mosquito susceptibility to arboviral infection [27,43,44]. Unfortunately, very little is known about the virome of the Aedes mosquitoes circulating in Cameroon [26,41,42] In this study, we employed viral metagenomics to characterize the viral composition of Aedes mosquito pools from four regions in the southwestern part of Cameroon representing three subclimatic zones (Table S1). In this part of the country, sampling showed that the dominant Aedes species was Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence show that ISVs interact with other components of the mosquito microbiota and influence mosquito susceptibility to arboviral infection [27,43,44]. Unfortunately, very little is known about the virome of the Aedes mosquitoes circulating in Cameroon [26,41,42] In this study, we employed viral metagenomics to characterize the viral composition of Aedes mosquito pools from four regions in the southwestern part of Cameroon representing three subclimatic zones (Table S1). In this part of the country, sampling showed that the dominant Aedes species was Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The eluted volume (60 μL) was diluted to 120 μL and divided into 10 aliquots of 12 μL each and stored to avoid multiple freeze thawing cycles of large volumes. The first aliquot was used for the amplification of the cytochrome c oxidase subunit I region of Aedes mosquitoes employing AUCOS primers (Table S2) with the QIAGEN One-step RT-PCR kit, following the manufacturer's protocol [42]. Briefly, the reaction mixture consisted of 10 μL RNase-free water, 5 μL of 5x QIAGEN OneStep RT-PCR Buffer, 1μL of dNTP Mix, 1.5 μL of each Primer (10 μM), 1μL of QIAGEN OneStep RT-PCR Enzyme Mix, and 5 μL of sample, in a total volume of 25 μL [41].…”
Section: Aedes Mosquito Identification and Quantification Of Selected...mentioning
confidence: 99%
“…Identification of mosquito species has become increasingly important in the last decades, due to the spread of (potentially) invasive species [ 1 ]. Container breeding mosquito species, which use natural or artificial containers for oviposition [ 2 ], are of particular concern due to their potential to be competent vectors for a variety of pathogens.…”
Section: Introductionmentioning
confidence: 99%